PREVALENCE OF IRON DEFICIENCY ANEMIA IN PEDIATRIC POPULATION AND ITS COGNITIVE EFFECTS: A SYSTEMATIC REVIEW AND META-ANALYSIS OF GLOBAL EVIDENCE. - Dena Nashaat Hamza; Roukaya Lamine Hamadi; Mohamed Idris; Wahid Ahmad Fayad Koudsi; Zahraa Mohammed Saeed Al Dujaili; Rida Ahmed; Gousiya Fathima; Nadya Hasan Rahman; Amal M-Bassam Adi; Adonis Khaled Abu Kariem; Shahad Alrashed; Anwar Abdullah Alghamdi; et al. (Journal of Population Therapeutics and Clinical Pharmacology, 2025)
Background: The common nutritional disorder iron deficiency anemia affects many children, resulting in cognitive and developmental damage to their health. knowledge about IDA prevalence together with its cognitive effects in children enables early detection along with appropriate intervention methods.Objective: The study conducts a systematic review with meta-analysis to determine the IDA rate in children and assess how it affects their cognitive abilities.Methodology: This study utilized PubMed as well as Scopus and Web of Science databases to search for studies that were published up to 2024. Research studies were included based on set entry requirements that studied both pediatric patients and cognitive changes. Random-effects models were used for meta-analysis to determine pooled prevalence and effect sizes in the analysis.Results: The scientific analysis included data from 28 research studies with a total of [insert sample size] participants. Data analysis showed that the total prevalence rate of IDA in children amounted to [insert percentage] % (95% CI: [insert CI]). Applications with IDA exhibited less productive mental performance than caffeine-absent children with a mean difference effect of [insert value] (p < 0.05).Conclusion: The widespread presence of IDA among children across the globe leads to considerable harm in their cognitive development processes. The essential approach to stop these adverse consequences requires early detection combined with prevention measures and suitable treatments.